Determination of fat-soluble dyes influence on the oxidation induction period of their oil solutions - Petik, Pavlo; Stankevych, Serhii; Zabrodina, Inna; Zhulinska, Oksana; Mezentseva, Iryna; Haliasnyi, Ivan; Hontar, Tatyana; Shubina, Lidiia; Kotliar, Oleh; Bondarenko, Svitlana (Eastern-European Journal of Enterprise Technologies, 2023)
The object of the study is the period of induction of accelerated oxidation of oil solutions of fat-soluble dyes chlorophyll and beta-carotene. The effect of the content of fat-soluble dyes on the period of induction of accelerated oxidation of their solutions in refined sunflower oil was studied. The peculiarity of the work consists in establishing approximate graphic and mathematical dependences of the term of the induction period of accelerated oxidation of refined sunflower oil on the content of chlorophyll and beta-carotene separately and together. This is important for predicting the shelf life of oil solutions of fat-soluble dyes. It was determined that chlorophyll A practically does not show a pro-oxidant effect if its content is up to 0.05 g/l. The content of chlorophyll A at the level of 0.10 g/l leads to a reduction in the duration of the induction period by 14 %; 0.20 g/l – by 36 %; 0.30 g/l – by 48 %. The content of beta-carotene at the level of 0.10 g/l leads to an increase in the duration of the induction period by 35 %; 0.20 g/l – by 47 %; 0.30 g/l – by 54 %. The content in the oil system of 0.10 g/l of beta-carotene and 0.05 g/l of chlorophyll A leads to a reduction in the period of induction of accelerated oxidation by 8.4 % compared to the oil solution of 0.10 g/l of beta-carotene without chlorophyll A. The obtained data are explained by the fact that there is a compensatory effect of the antioxidant beta-carotene on the pro-oxidant effect of chlorophyll A in the oil solution. A feature of the obtained results is the possibility of predicting the shelf life of oil solutions of fat-soluble dyes. From a practical point of view, the results of the research allow to develop oil systems taking into account the separate and compatible features of reactivity to the oxidation of chlorophyll and beta-carotene. An applied aspect of using the scientific result is the possibility of expanding the assortment of oil products of increased nutritional value with different contents of chlorophyll and beta-carotene